2022
DOI: 10.13189/eer.2022.100604
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Metals in Mangrove Snail (Cerithidea obtusa) from Southwest Johor, Malaysia

Abstract: Pollutants are persistent in the environment, taint the food chain, and harm people's health because of their toxicity. In this study, mangrove snails called Cerithidea obtusa (C. Obtusa) were gathered from Southwest Johor, Malaysia, and the amounts of macro and micro elements Ca, Fe, K, Mg, Na, As, Mn, and Zn in their soft tissues, shells, and related surface sediments were analysed. The Neutron Activation Analysis (NAA) method was used to calculate the elements concentration. The mean concentrations of Ca,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The strong association shows that the concentrations of these metals are consistent with the origins of the trace elements. Anthropogenic sources are the main contributing source of trace elements in places with mangroves [2,28].…”
Section: Resultsmentioning
confidence: 99%
“…The strong association shows that the concentrations of these metals are consistent with the origins of the trace elements. Anthropogenic sources are the main contributing source of trace elements in places with mangroves [2,28].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the snails are sold locally and are highly consumed by Malaysians since the snails can be found in most local markets. Studies on potentially toxic metals in the mangrove snails have been reported in the literature [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. In particular, biomonitoring using C. obtusa was reported from Indonesia [ 31 , 43 , 45 , 49 ], Malaysia [ 46 , 47 , 49 , 50 , 59 , 60 ], Vietnam [ 57 ] and India [ 48 , 52 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on potentially toxic metals in the mangrove snails have been reported in the literature [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. In particular, biomonitoring using C. obtusa was reported from Indonesia [ 31 , 43 , 45 , 49 ], Malaysia [ 46 , 47 , 49 , 50 , 59 , 60 ], Vietnam [ 57 ] and India [ 48 , 52 , 54 ]. However, there has been no discussion on the connection between the water–energy–seafood nexus and PTM biomonitoring in the edible mangrove snails.…”
Section: Introductionmentioning
confidence: 99%